Pemodelan dan Verifikasi Formal Protokol EE-OLSR dengan UPPAAL CORA - Rachmat Wahid Saleh Insani; Reza Pulungan (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2016)
Information and Communication Technology systems is a most important part of society. These systems are becoming more and more complex and are massively encroaching on daily life via the Internet and all kinds of embedded systems. Communication protocols are one of the ICT systems used by Internet users. OLSR protocol is a wireless network communication protocol with proactive, and based on link-state algorithm. EE-OLSR protocol is a variant of OLSR that is able to prolong the network lifetime without losses of performance.Protocol verification process generally be done by simulation and testing. However, these processes unable to verify there are no subtle error or design flaw in protocol. Model Checking is an algorithmic method runs in fully automatic to verify a system. UPPAAL is a model checker tool to model, verify, and simulate a system in Timed Automata.UPPAAL CORA is model checker tool to verify EE-OLSR protocol modelled in Linearly Priced Timed Automata, if the protocol satisfy the energy efficient property formulated by formal specification language in Weighted Computation Tree Logic syntax. Model Checking Technique to verify the protocols results in the protocol is satisfy the energy efficient property only when the packet transmission traffic happens.